2022
DOI: 10.7150/thno.68895
|View full text |Cite
|
Sign up to set email alerts
|

M2 microglia-derived extracellular vesicles promote white matter repair and functional recovery via miR-23a-5p after cerebral ischemia in mice

Abstract: Rationale: White matter repair is critical for the cognitive and neurological functional recovery after ischemic stroke. M2 microglia are well-documented to enhance remyelination and their extracellular vesicles (EVs) mediate cellular function after brain injury. However, whether M2 microglia-derived EVs could promote white matter repair after cerebral ischemia and its underlying mechanism are largely unknown. Methods: EVs were isolated from IL-4 treated microglia (M2-EVs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 68 publications
3
45
0
1
Order By: Relevance
“…These results were corroborated by another independent study, showing that intravenous delivery of pro-regenerative microglial EVs significantly promoted OL maturation and white matter structural remodeling after transient MCAo (Li et al, 2022b). In both cases, microglial EVs were able to successfully promote remyelination and long-term functional recovery after stroke (Raffaele et al, 2021;Li et al, 2022b).…”
Section: The Impact Of Microglia-derived Extracellular Vesicles On Ol...supporting
confidence: 69%
See 2 more Smart Citations
“…These results were corroborated by another independent study, showing that intravenous delivery of pro-regenerative microglial EVs significantly promoted OL maturation and white matter structural remodeling after transient MCAo (Li et al, 2022b). In both cases, microglial EVs were able to successfully promote remyelination and long-term functional recovery after stroke (Raffaele et al, 2021;Li et al, 2022b).…”
Section: The Impact Of Microglia-derived Extracellular Vesicles On Ol...supporting
confidence: 69%
“…In this respect, infusion of pro-regenerative microglial EVs in the ipsilateral corpus callosum of ischemic mice was found to significantly increase OPC recruitment at lesion boundaries and enhance their maturation (Raffaele et al, 2021 ). These results were corroborated by another independent study, showing that intravenous delivery of pro-regenerative microglial EVs significantly promoted OL maturation and white matter structural remodeling after transient MCAo (Li et al, 2022b ). In both cases, microglial EVs were able to successfully promote remyelination and long-term functional recovery after stroke (Raffaele et al, 2021 ; Li et al, 2022b ).…”
Section: The Impact Of Microglia-derived Extracellular Vesicles On Ol...supporting
confidence: 64%
See 1 more Smart Citation
“…Proteomic analysis of microglial EVs has been performed on different samples: EVs from N9 ( Potolicchio et al, 2005 ) and BV2 ( Yang et al, 2018 ) cell lines, primary rat microglia ( Hooper et al, 2012 ; Drago et al, 2017 ; Mukherjee et al, 2020 ), MACS sorted rat microglia ( Murgoci et al, 2020 ), primary leech microglia ( Arab et al, 2019 ; Lemaire et al, 2019 ), microglia-like cells from human iPSCs ( Mallach et al, 2021a , b ; You et al, 2022 ), CD11b + EVs from human brain tissue ( Cohn et al, 2021 ). Their lipid ( Osteikoetxea et al, 2015 ; Cohn et al, 2021 ; Kumar et al, 2021 ) and small non-coding RNA (miRNA) composition ( Cunha et al, 2016 ; Prada et al, 2018 ; Lemaire et al, 2019 ; Tian et al, 2019 ; Cohn et al, 2021 ; Li et al, 2022 ) have also been investigated. A summary of these studies is reported in Table 2 .…”
Section: Composition Of Microglial Extracellular Vesiclesmentioning
confidence: 99%
“…A few studies have analyzed the miRNA cargo of microglial EVs. Sequencing studies identified 41 miRNAs differentially expressed in small EVs isolated from IL-4 polarized BV2 cells compared to unstimulated controls, including some upregulated miRNAs (miR-23a-5p, miR-221-3p, miR-129-5p) involved in oligodendrogenesis ( Li et al, 2022 ). Moreover, an independent study compared the miRNA profiles of small EVs from unpolarized, LPS-polarized and IL-4-polarized BV2 cells, detecting a specific enrichment of the proangiogenic miR-26a in pro-regenerative EVs with respect to the other two conditions ( Tian et al, 2019 ).…”
Section: Composition Of Microglial Extracellular Vesiclesmentioning
confidence: 99%